2000
DOI: 10.1023/a:1007509608440
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Fibrillar amyloid beta-protein (Abeta) is the major protein of amyloid plaques in the brains of patients with Alzheimer's disease (AD). The mechanism by which normally produced soluble Abeta gets fibrillized in AD is not clear. We studied the effect of neutral, zwitterionic, and anionic lipids on the fibrillization of Abeta 1-40. We report here that acidic phospholipids such as phosphatidic acid, phosphatidylserine, phosphatidylinositol (PI), PI 4-phosphate, PI 4,5-P2 and cardiolipin can increase the fibrilliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 37 publications
7
42
1
Order By: Relevance
“…It is therefore considered that the Aβ fibrils can be regarded as a crystal-like aggregate. Fibril growth behavior of Aβ in the presence of copper (II) ion and liposomes It has been reported that the fibril growth of Aβ was affected by the copper (II) ion [22][23][24][25] and the liposomes [10,17,18]. It seems that those factors could affect both the nucleation and elongation steps.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore considered that the Aβ fibrils can be regarded as a crystal-like aggregate. Fibril growth behavior of Aβ in the presence of copper (II) ion and liposomes It has been reported that the fibril growth of Aβ was affected by the copper (II) ion [22][23][24][25] and the liposomes [10,17,18]. It seems that those factors could affect both the nucleation and elongation steps.…”
Section: Resultsmentioning
confidence: 99%
“…The excess copper (II) ion (Aβ:Cu II = 1:20) considerably inhibited the increase in ThT fluorescence intensity. Alternatively, the liposome could affect the fibril growth [10,17,18]. In order to investigate whether the liposome was effective in the elongation step, a growth behavior of seeds of Aβ fibrils was studied in the presence of the copper (II) ion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of antibacterial antibiotics, polar head groups often play an important role for their selective toxicity. [20][21][22][23][24] The membrane-permeabilizing antibiotics have been studied using artificial liposomes with various methods. 19,[23][24][25][26][27][28][29] Among them, a fluorometric method using dye-encapsulated liposomes is effective for the real-time monitoring of ion flux, which enable the detection of minute difference in the activity.…”
Section: Introductionmentioning
confidence: 99%